Marketing places and spaces - Correia, Anto<U+0301>nia. (Bingley, U.K. : Emerald, 2015)
Marketing places and spaces covers a broad range of issues that hospitality and tourism executives will benefit from addressing, but frequently forget to do so. To provide an indication of the broad range and exciting coverage of issues, here are a few titles of the 21 chapters in the volume: Conceptualizing the Value Co-creation Challenges for Tourist Destinations: a Supply-Side Perspective; The Emotional Attachment Built through the Attitudes and Managerial Approach to Place Marketing and Branding - The Golden City of Kremnica, Slovakia; Events as a Differentiation Strategy for Tourist Destinations; How do Tourists Turn Space into Place? - A Conceptualisation for Sustainable Place Marketing; the Influence of Slow City in the Context of Sustainable Destination Marketing; Wedding-based Tourism Development: Insights from an Italian Context. Authors include tourism researchers working in Finland, UK, Macau, Japan, New Zealand, and beyond. A practical strategy guide and an in-depth complement with extensions to Elizabeth Gilbert's "Eat Pray Love" for hospitality and tourism professionals and educators is the relevant perspective that "Marketing Places and Spaces" provides.
Local students' perceptions of spaces for tourists and locals in a shopping district : photo-based research / Taketo Naoi ... [et al.] -- Residents' perceptions of mountain destinations / Carla Silva, Elisabeth Kastenholz, Jose<U+0301> Abrantes -- Attitudes of successors in dairy farms toward educational tourism in Japan / Yasuo Ohe -- Residents' perceptions of the impact of ship tourism and their preferences for different types of tourism / Giacomo Del Chiappa, Giuseppe Melis -- Wedding-based tourism development : insights from an Italian context / Giacomo Del Chiappa, Fulvio Fortezza -- Conceptualizing the value co-creation challenge for tourist destinations : a supply-side perspective / Giuseppe Melis, Scott McCabe, Giacomo Del Chiappa -- The emotional attachment built through the attitudes and managerial approach to place marketing and branding "The golden city of Kremnica, Slovakia" / Marica Mazurek -- Hospitality servicescapes seen by visually impaired travelers / Alma Raissova -- Determinants of tourism destination competitiveness : an SEM approach / Cristina Esteva<U+0303>o, Joa<U+0303>o Ferreira, Sara Nunes -- Events as a differentiation strategy for tourist destinations : the case of Allgarve / Ine<U+0302>s Miranda, Nuno Gustavo, Euge<U+0301>nia Castela -- From tourism space to a unique tourism place through a conceptual approach to building a competitive advantage / Kamila Borsekova<U+0301>, Anna Vanova<U+0301>, Katari<U+0301>na Petri<U+0301>kova<U+0301> -- Achieving consistency in destination personalities : a tripartite personality congruity theory focused on industry professionals / Veronica I.K. Lam,Leonardo (Don) A.N. Dioko -- Marketing to children in tourism industry : descriptive analysis of kid-friendly hotels' practices In Turkey / C<U+0327>agil Hale O<U+0308>zel -- The influence of slow city in the context of sustainable destination marketing / Yesim Cosar, Alp Timur, Metin Kozak -- Customer communication facilities with tourism : a comparison between German and Japanese automobile companies / Yosuke Endo,Yohei Kurata -- Tourist spaces and tourism policy in Spain and Portugal / Fernando Almeida, Rafael Corte<U+0301>s, Antonia Balbuena -- Analyzing seasonal differences in a destination's tourist market : the case of Minho / Elisabeth Kastenholz, Anto<U+0301>nio Lopes de Almeida -- Modelling ferry passenger numbers : implications for destination management / Carl H. Marcussen -- Yielding tourists' preferences / Jaime Serra, Anto<U+0301>nia Correia, Paulo M.M. Rodrigues -- Lake-destination image attributes : content analysis of text and pictures / Ana Isabel Rodrigues ... [et al.] -- How do tourists turn space into place? A conceptualisation for sustainable place marketing / Juergen Gnoth.
Print version record
Keywords: Business & Economics -- Industries -- Hospitality, Travel & Tourism; Tourism industry; Tourism -- Marketing; Tourism -- Research